Anti-Windup Strategy Based on Back Calculation and Tracking Applied to Direct PID Fuzzy Controllers - Rodriguez-Castellanos, Jhon Edisson; Cote-Ballesteros, Jorge Eduardo (Universidad Pedagógica y Tecnológica de Colombia, 2019)
Recently, direct fuzzy PID controllers have been used more frequently in industrial continuous process applications, because they can replace the conventional PID within the control loop, since its non-linear behavior, presents an adequate performance in control tasks applied to processes nonlinear. However, PID controllers are affected by the phenomenon called windup which degrades the performance of the controller to the accumulation of error in the integral component. This article presents a proposal of an anti-windup scheme based on back calculation and tracking, for which the tracking constant is obtained through the tuning parameters of the fuzzy PID controller. The tuning method used for this document consists in the adjustment of the control surface by means of the scale gains of the architectures considered. In addition, the validation of the proposed anti-windup method performance is carried out through a comparative analysis against other classic techniques. The proposed strategy shows an adequate performance against changes in the reference and rejection of disturbances without tuning additional parameters. An analysis of the control effort shows the proposed strategy produces control actions smaller than the other cases considered. Therefore, due to the increasing popularity of fuzzy systems in the industry and the simplicity of some design methods, the proposed strategy can be easily implemented in different industrial regulators.